Methods of Managing Postoperative Pain in Orthopedics - Kupczak, Agata; Zając, Kacper; Uchto, Adrian; Kozioł, Mateusz; Górka, Dariusz; Palacz, Karolina Alicja (Quality in Sport, 2024)
Postoperative pain management is a critical concern for patients undergoing orthopedic procedures, impacting both recovery and overall patient satisfaction. Effective pain control is essential for minimizing complications such as limited mobility and delayed healing. This paper reviews contemporary strategies for managing postoperative pain in orthopedics, focusing on both pharmacological and non-pharmacological approaches. Pharmacotherapy, including nonsteroidal anti-inflammatory drugs (NSAIDs) and opioids, is commonly utilized but must be carefully managed to prevent adverse effects such as dependence and gastrointestinal issues. Complementing these methods, non-pharmacological interventions such as physical therapy, cryotherapy, transcutaneous nerve stimulation, and music therapy offer holistic benefits without the associated risks of medication. The study emphasizes the importance of a multifaceted approach that includes early rehabilitation and patient education to enhance recovery outcomes. The combined use of diverse pain management techniques can optimize analgesic efficacy while promoting patient comfort and reducing hospital stays, ultimately leading to improved rehabilitation results.